2022
DOI: 10.1111/cas.15256
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of TERT aberrations in myxoid liposarcoma: TERT reactivation may play a crucial role in tumorigenesis

Abstract: Myxoid liposarcoma (MLPS) is genetically characterized by FUS‐DDIT3 or EWSR1‐DDIT3 gene fusion and the high frequency of hotspot mutations (C228T or C250T) in the promoter region of telomerase reverse transcriptase (TERT) that encodes the TERT protein. The latter leads to telomerase reactivation, a mechanism of telomere maintenance. Although the TERT promoter hotspot mutation is a poor prognostic factor in various tumors, its effect on MLPS has not been reported in detail. In the present study, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…11,12 Despite recent advances in surgery, radiotherapy, and novel treatment strategies, the overall 5-year survival rate of patients with RPLs remains at approximately 50%. 13,14 In previous studies, a large number of clinical and histopathological features and therapeutic strategies have been investigated to predict and improve the prognosis of RPLs. [15][16][17][18][19][20] With the increased understanding of human health and the consequent advancements in healthcare, the role of socio-psychosocial factors in cancer is receiving increased attention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Despite recent advances in surgery, radiotherapy, and novel treatment strategies, the overall 5-year survival rate of patients with RPLs remains at approximately 50%. 13,14 In previous studies, a large number of clinical and histopathological features and therapeutic strategies have been investigated to predict and improve the prognosis of RPLs. [15][16][17][18][19][20] With the increased understanding of human health and the consequent advancements in healthcare, the role of socio-psychosocial factors in cancer is receiving increased attention.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have demonstrated that novel therapeutic strategies, including targeted drugs, are effective for treating RPLs 11,12 . Despite recent advances in surgery, radiotherapy, and novel treatment strategies, the overall 5‐year survival rate of patients with RPLs remains at approximately 50% 13,14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomerase reverse transcriptase (TERT) promoter mutation has been found in human hepatobiliary, pancreatic, and gastrointestinal cancer cell lines (Hirata et al, 2022). The high frequency of hotspot mutations (C228T or C250T) in the promoter region of telomerase reverse transcriptase TERT that encodes the TERT protein has also been found in myxoid liposarcoma (Kunieda et al, 2021). PinX1, known as a potent TERT inhibitor, also contributes to cellular aging and cancer tumorigenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, two popular mutation sites, C228T and C250T, were also found in adrenal tumors, which can promote the expression of hTERT and increase the activity of telomerase, providing a suitable environment for tumor growth [25]. In addition, scientists have successively found mutations in the hTERT promoter region in thyroid cancer [26], liposarcoma [27], hepatocellular carcinoma [28], urothelial cancer and other tumors [29,30], but the mutation sites and mutation frequencies were not the same. Since the first discovery of TERT promoter mutations in melanoma, an increasing number of studies have shown that TERT promoter mutations play an important role in tumorigenesis [31,32].…”
Section: Introductionmentioning
confidence: 99%